Treatment of systemic sclerosis–associated interstitial lung disease: Lessons from clinical trials. Issue 2 (March 2020) - Roofeh, David; Distler, Oliver; Allanore, Yannick; Denton, Christopher P; Khanna, Dinesh
Systemic sclerosis–associated interstitial lung disease remains a leading cause of mortality. Despite decades of clinical trials, the treatment effects of disease modifying anti-rheumatic drugs continue to be modest and there remains a great need for therapies that attenuate and hopefully ameliorate parenchymal lung disease. In this review, we highlight the key clinical trials that have shaped the management strategies employed by the authors, providing their strength of recommendation based on level of evidence. We also review lessons learned in more recent years, suggesting a benefit in targeting patients with subclinical interstitial lung disease with high risk for progression early in the disease course, as well as the benefit seen in a large clinical trial leading to the first Food and Drug Administration–approved treatment for systemic sclerosis–associated interstitial lung disease. These lessons come in a context of heterogeneity of patient populations and response to therapy, as well as the inherent constraints of time-limited studies to detect meaningful outcomes for patients.